Defectivitat morfològica i variació sintàctica - Gallego, Àngel J. (Caplletra. Revista Internacional de Filologia, 2007)
This paper discusses a case of parametric variation between Catalan and Spanish that concerns the fronting possibilities within the CP domain (the so-called ÇLeft PeripheryÈ). In particular, attention is paid to Catalan’s weak left peripheral activity, which prevents it from generating sentences that involve a Çmild focalizationÈ pattern very common in Spanish (e.g., «Mucha tontería dice el Gobierno» vs. *«Molta ximpleria diuel Govern»), first noted by Torrego (1980) and further explored by Uriagereka (1988). Interestingly, the same behavior is observed in the v*P domain, which accounts for the fact that VSO sentences (generated through movement of the subject to a specifier position, as Ordóñez 2005; this volume contends) are barred in Catalan, but not in Spanish. It is argued that the relevant micro-parameter has to do with Çmorphological defectivityÈ, not in the sense of Chomsky (2000; 2001) (where such notion is related to the absence of abstract _-features), but in a more morpho-phonological one whereby defectivity follows from having a poorer (explicit) manifestation of features: morphological defectivity of a verbal paradigm weakens both verb movement and peripheral fronting.